Management of nail psoriasis. (2nd August 2020) - Thomas, L.; Azad, J.; Takwale, A.
Summary: Nail involvement is estimated to affect 80–90% of patients with psoriasis at some point in their lives and is often associated with severe disease. Patients with nail involvement experience pain, functional impairment and social stigma, with significant restriction of daily activities and quality of life. Nail psoriasis is also considered a risk factor for the development of psoriatic arthritis (PsA). Management of nail psoriasis is deemed challenging and as a result, it is often left untreated by physicians. Assessing the severity of nail disease can also be difficult in clinical practice. While the Nail Psoriasis Severity Index is used widely in trials, it is time‐consuming and rarely used in the clinic, highlighting the need to develop a simplified disease severity score for nail psoriasis. All patients should be advised to keep their nails short, wear gloves for wet and dirty work, and regularly apply emollient to the nail folds and nail surface. Patients with mild nail psoriasis, without signs of severe cutaneous psoriasis or PsA, may benefit from topical treatment, while systemic treatment is indicated in patients with severe nail involvement. Evidence suggests that all anti‐tumour necrosis factor (TNF)‐α, anti‐interleukin (IL)‐17, and anti‐IL‐12/23 antibodies available for plaque psoriasis and PsA are highly effective treatments for nail psoriasis. This article aims to provide an up‐to‐date review of the therapeutic options currently available for the management of nail psoriasis in patients with or without skin psoriasis. Therapeutic options for the management of nail psoriasis in children will also be discussed.